Improving Business Synergy Between PT.Krakatau Steel (Persero)Tbk and PT.Krakatau Wajatama using byproduct Billet Steel Plant To Increase Consolidated Profit - Gupito, Wedo; Larso, Dwi (The Indonesian Journal of Business Administration, 2013)
PT.Krakatau Wajatama is subsidiary 100% owned by PT.Krakatau Steel (Persero) Tbk, doing business in production and distribution steel reinforcing rebars. Marketed using marking Ã¢â‚¬Å“KSÃ¢â‚¬Â, the product having strong positioning as a steel reinforcing rebars which can lowering risk the building structure damaged impacted by fire and earthquake disasters. Market area are covered jabodetabek, banten, west jawa and parts of sumatera islands. PT.Krakatau Wajatama have no upstream of raw material production facility and having limitation in production capacity and product variances resulted. Facing with those contsraints, how PT.Krakatau Wajatama can increase its profit as well as consolidated profit for PT.Krakatau Steel (Persero) Tbk.Ã‚Â The final project starts by conducting value chain analysis of entire flow activities in PT.Krakatau Wajatama and main activity flow in Billet Steel Plant PT.Krakatau Steel (Persero) Tbk, and PT.Delco Prima Pasific, to find out opportunity to increase profit. The analysis finds an opportunity to increase profit through improving business synergy between PT.Krakatau Steel (Persero) Tbk and PT.Krakatau Wajatama using byproduct of Billet Steel Plant PT.Krakatau Steel (Persero) Tbk. Furthermore the project is collecting primary data which are production volume and transfer price of byproduct Billet Steel Plant PT.Krakatau Steel (Persero) Tbk, join production fee in PT.Delco Prima Pasific and product selling price of PT.Krakatau Wajatama, and conducting simulation using Microsoft Excel 2007 upon every possible alternatives solution to carry out best alternative. The simulation shows that synergy sales alternative between PT.Krakatau Steel (Persero) Tbk and PT.Krakatau Wajatama is giving potential of increasing in consolidated profit with total amount Rp.861.003.983,- per month, which is the highest value compares to other alternative. Therefore the project proposed this alternative as business solution.Ã‚Â Key Word: Krakatau Wajatama, value chain analysis, by product, consolidated profit.